What if? The effects of a hard decoupling from China on the German economy - David Baqaee; Julian Hinz; Benjamin Moll; Moritz Schularick; Feodora A. Teti; Joschka Wanner; Sihwan Yang (Kiel Institute for the World Economy (IfW Kiel), 2024)
How would the German economy cope with a hard economic decoupling from China? The authors study a scenario where the global economy fragments into three distinct blocs: the G7 economies and their allies, China and her allies, as well as neutral countries. German trade with China would have to be entirely rerouted to countries within the "Western" block and neutral countries. The authors quantify the costs of such a worst-case hard decoupling using the (Baqaee and Farhi 2021) multi-sector model of the world economy. The key finding is that a total cut-off of trade relations with China would have severe but not devastating effects on the German economy. The welfare loss for Germany (relative to a no-cut-off baseline) would be around 5 percent of Gross National Expenditure (GNE) over the first few months and around 4 percent over the first year, plus additional short run costs due to business-cycle amplification effects. In the medium and long run, the costs would fall to a permanent loss in the 1-2 percent range. Less extreme decoupling or gradual de-risking scenarios ("small yard, high fence") would incur smaller costs. The single most influential assumption relates to the "trade elasticity,", i.e., the ease and speed with which trade can be reorganized away from China to neutral countries and within the "Western" block. The authors' findings, in particular the critical dependence of economic costs on the time horizon over which adjustments take place, provide some rationale for embarking on a gradual de-risking trajectory to avoid a costly and politically contentious hard decoupling dictated by geopolitical events. – – Wie würde die deutsche Wirtschaft eine harte wirtschaftliche Abkopplung von China bewältigen? Um dem nachzugehen, simulieren die Autoren mithilfe eines quantitativen Handelsmodels ein Szenario, in dem sich die Weltwirtschaft in drei Blöcke aufspaltet: die G7-Staaten und ihre Verbündeten, China mit seinen Verbündeten sowie neutrale Länder. Der Handel Deutschlands mit China müsste komplett auf Länder des "westlichen" Blocks und neutrale Staaten umgeleitet werden. Die Kosten einer solchen worst-case harten Entkopplung quantifizieren die Autoren mit dem Multisektor-Modell der Weltwirtschaft von Baqaee und Farhi (2021). Die zentrale Erkenntnis der Autoren ist, dass ein vollständiger Abbruch der Handelsbeziehungen mit China schwerwiegende, aber nicht katastrophale Auswirkungen auf die deutsche Wirtschaft haben würde. Der Wohlfahrtsverlust für Deutschland würde sich in den ersten Monaten auf etwa 5 Prozent des Bruttonationaleinkommens (BNE) belaufen und im Laufe des ersten Jahres auf etwa 4 Prozent sinken, zusätzlich zu weiteren kurzfristigen Kosten durch konjunkturelle Verstärkungseffekte. Mittel- bis langfristig würden die Kosten auf einen dauerhaften Wohlstandsverlust von 1-2 Prozent zurückgehen. Weniger extreme Abkopplungsvarianten oder eine schrittweise Risikominimierung ("small yard, high fence") würden geringere Kosten verursachen. Die wichtigste Annahme in der Simulation betrifft die Handelselastizität, also die Leichtigkeit und Geschwindigkeit, mit der der Handel von China auf neutrale Länder und innerhalb des westlichen Blocks umgestellt werden kann. Die Ergebnisse des Policy Briefs, insbesondere die deutliche Abhängigkeit der wirtschaftlichen Kosten vom Anpassungszeitraum, bieten Argumente für einen schrittweisen Risikominimierungspfad, um eine teure und politisch kontroverse harte Abkopplung zu vermeiden, die durch geopolitische Ereignisse erzwungen werden könnte.
Keywords: 330; De-risking; Decoupling; Sanctions; Embargoes; De-Risking; Entkopplung; Sanktionen; Embargos